Use of Favipiravir in Covid-19 Patients: A Narrative Review - Vitarani Dwi Ananda Ningrum; Annisa Fitria; Fadiyah Ulfa Hanur (Universitas Sebelas Maret, 2024)
COVID-19 is an acute respiratory disease resulting from the infection of SARS-COV-2 viruses and causes high morbidity, which requires appropriate treatment targets. Favipiravir is an antiviral that selectively inhibits RNA-dependent RNA polymerase (RdRp) of virus. This review aimed to identify several studies that prove the effectiveness and safety of using Favipiravir for COVID-19 patients. The search method used the electronic media PubMed and ScienceDirect with the keywords